DAMPAK NEGATIF PENGGUNAAN GADGET PADA PESERTA DIDIK SMP NEGERI 13 PONTIANAK - Julita, Marcellina; Yuline, Yuline; Yusuf, Abas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractGadget have many positive effect for children to search education books, for open mind and to see the world in a one screen. Beside on that positive effect, gadget have too many negative effect for children grows. The goals of researcher is want to knowmore deep about the negative effect of using gadget at SMP 13 Pontianak class 8. Researcher using descriptive methods on this research. Using interview the client, quistionaire, and documentation. We also use the data reduction, giving data and triangulation data. Depends on this analyst data show us what is the negative effect of using gadget is lose weight, because too long playing game can be distract us to doing another things, they like to lie others, lazy to do homeworks, don?t come to school, bully each others, and be so don?t polite to each others. Researcher hope that this research can be so effective to change student at SMPN 13 Pontianak, be more productive better than all day using gadget to playing game, watch youtube, seeing social media and etc. Tesearchet hope too the teachers of SMPN 13 Pontianak can be hardworking to teachs and explain the student about this negativity effect and can change this bad behavior of students.Keywords: Gadget, Negative Effect